2021
DOI: 10.3390/pathogens10060691
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Local Transmission Dynamics of Highly Pathogenic Avian Influenza H5N6 in the Republic of Korea by Integrating Phylogenetic Information

Abstract: Highly pathogenic avian influenza (HPAI) virus is one of the most virulent and infectious pathogens of poultry. As a response to HPAI epidemics, veterinary authorities implement preemptive depopulation as a controlling strategy. However, mass culling within a uniform radius of the infection site can result in unnecessary depopulation. Therefore, it is useful to quantify the transmission distance from infected premises (IPs) before determining the optimal area for preemptive depopulation. Accordingly, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…Two recent studies have estimated the effective culling radius based upon the 2016–2017 HPAI outbreak in Korea [ 21 , 23 ]. In both Yoo et al [ 21 ] and Lee et al [ 23 ], the analyses were focused upon the same general time period of the 2016–2017 outbreak and were constrained to Chungbuk in Korea containing higher densities of duck farms. Thus, conclusions from these previous studies may be particular to that region and time period during the 2016–2017 HPAI outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two recent studies have estimated the effective culling radius based upon the 2016–2017 HPAI outbreak in Korea [ 21 , 23 ]. In both Yoo et al [ 21 ] and Lee et al [ 23 ], the analyses were focused upon the same general time period of the 2016–2017 outbreak and were constrained to Chungbuk in Korea containing higher densities of duck farms. Thus, conclusions from these previous studies may be particular to that region and time period during the 2016–2017 HPAI outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 23 ] estimated an effective culling radius of 2.24 km, when not considering spatial heterogeneity, and 2.65 km when spatial heterogeneity, represented by the local reproductive numbers of the virus, was considered. Yoo et al [ 21 ] simulated the risk for the local transmission of HPAI based upon the heterogeneity of the different clusters as determined by the genotype of the viruses and, although not conclusive, suggested that culling radii between 2–3 km are more appropriate, but only in areas with high densities of duck farms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This formula has been tested many times, and the data selection search bandwidth is 333.6 km to more intuitively reflect the spatial distribution of sports tourism resources. Yoo et al [14] and Allen et al [15] made use of kernel density in order to determine the center position of a specific element. The density is the highest at the center position, and it decays with distance.…”
Section: Kernel Densitymentioning
confidence: 99%